2018
DOI: 10.1007/s10147-018-1247-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic findings of high-grade cervical intraepithelial neoplasia or more on magnifying endoscopy with narrow band imaging

Abstract: The lesions ≥ CIN 3 demonstrated characteristic ME-NBI findings of h-WE alone, or l-/h-WE with atypical micro-vessels. This study indicates that ME-NBI may have novel value for CIN diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Our previous study found that the diagnostic criteria for CIN3 under ME-NBI were: the presence of a thick or thin white epithelium plus atypical vessels or dense acetowhite epithelium grade 2 [9]. Both the present cases met the diagnostic criteria for CIN3 under ME-NBI.…”
Section: Figuressupporting
confidence: 71%
See 1 more Smart Citation
“…Our previous study found that the diagnostic criteria for CIN3 under ME-NBI were: the presence of a thick or thin white epithelium plus atypical vessels or dense acetowhite epithelium grade 2 [9]. Both the present cases met the diagnostic criteria for CIN3 under ME-NBI.…”
Section: Figuressupporting
confidence: 71%
“…Magnifying endoscopy with narrow-band imaging (ME-NBI) has excellent diagnostic ability for early squamous cell carcinoma in the esophagus, and the head and neck region [7]. Our previous investigations demonstrated that ME-NBI was efficacious for evaluating the micro-vascular pattern [8] as well as white epithelium [9] of CIN. In the CIN appearance, the micro-vessels under ME-NBI correspond to punctuation and a mosaic pattern in colposcopy findings.…”
Section: Figuresmentioning
confidence: 99%
“…Endocytoscopy might be useful for determination of the need for conization. Recently, there have been a few reports on the usefulness of flexible magnifying endoscopy with narrow band imaging (ME-NBI) for evaluation of CIN [15,16]. ME-NBI visualizes microstructures of the mucosa showing microvascular features with 80-100-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been a few reports on the usefulness of exible magnifying endoscopy with narrow band imaging (ME-NBI) for evaluation of CIN [15,16]. ME-NBI visualizes microstructures of the mucosa showing microvascular features with 80-100-fold.…”
Section: Discussionmentioning
confidence: 99%